LFA-1 Engagement Triggers T Cell Polarization at the HIV-1 Virological Synapse - Starling, Shimona (J Virol, 2016)
HIV-1 efficiently disseminates by cell-cell spread at intercellular contacts called virological synapses (VS), where the virus preferentially assembles and buds. Cell-cell contact triggers active polarization of organelles and viral proteins within infected cells to the contact site to support efficient VS formation and HIV-1 spread; critically, however, which cell surface protein triggers contact-induced polarization at the VS remains unclear. Additionally, the mechanism by which the HIV-1 envelope glycoprotein (Env) is recruited to the VS remains ill defined. Here, we use a reductionist bead-coupled antibody assay as a model of the VS and show that cross-linking the integrin LFA-1 alone is sufficient to induce active T cell polarization and recruitment of the microtubule organizing center (MTOC) in HIV-1-infected cells. Mutant cell lines coupled with inhibitors demonstrated that LFA-1-induced polarization was dependent on the T cell kinase ZAP70. Notably, immunofluorescent staining of viral proteins revealed an accumulation of surface Env at sites of LFA-1 engagement, with intracellular Env localized to a Golgi compartment proximal to the polarized MTOC. Furthermore, blocking LFA-1-induced MTOC polarization through ZAP70 inhibition prevented intracellular Env polarization. Taken together, these data reveal that LFA-1 is a key determinant in inducing dynamic T cell remodeling to the VS and suggest a model in which LFA-1 engagement triggers active polarization of the MTOC and the associated Env-containing secretory apparatus to sites of cell-cell contact to support polarized viral assembly and egress for efficient cell-cell spread. IMPORTANCE HIV-1 causes AIDS by spreading within immune cells and depletion of CD4 T lymphocytes. Rapid spread between these cells occurs by highly efficient cell-cell transmission that takes place at virological synapses (VS). VS are characterized by striking T cell remodeling that is spatially associated with polarized virus assembly and budding at sites of cell contact. Here, we show that the integrin LFA-1 triggers organelle polarization and viral protein recruitment, facilitating formation of the VS, and that this requires the T cell kinase ZAP70. Taken together, these data suggest a mechanism by which HIV-1-infected T cells sense and respond to cell contact to polarize viral egress and promote cell-cell spread. Understanding how cell-cell spread is regulated may help reveal therapeutic targets to specifically block this mode of HIV-1 dissemination.